[123I]-IMP single-photon emission computed tomography imaging in visual snow syndrome: A case series. (December 2020) - Shibata, Mamoru; Tsutsumi, Kei; Iwabuchi, Yu; Kameyama, Masashi; Takizawa, Tsubasa; Nakahara, Tadaki; Fujiwara, Hirokazu; Jinzaki, Masahiro; Nakahara, Jin; Dodick, David W
Background: Visual snow syndrome (VSS) is a neurological condition characterized by persistent flickering dots in the visual fields, palinopsia, enhanced entoptic phenomenon, photophobia, and nyctalopia. Neuroimaging evidence supports the role of the visual association cortex in visual snow syndrome. Case series: We provided clinical care to three patients with visual snow syndrome, in whom [ 123 I]-IMP single-photon emission computed tomography (SPECT) imaging was performed. Case 1 was a 21-year-old male with a past history of migraine with aura who exhibited visual snow and entoptic phenomenon. In this patient, [ 123 I]-IMP SPECT imaging revealed right occipital and temporal hypoperfusion with a distribution matching the ventral visual stream. [ 123 I]-IMP SPECT imaging detected only mild bilateral frontal hypoperfusion in Case 2 and no overt abnormalities in Case 3. Conclusion: Although visual snow syndrome seems to be a heterogenous condition, our observations indicate that abnormal visual processing within the ventral visual stream may play a role in the pathogenesis of this condition.